Banking in Cyprus: its road to EU and Euro adaptation - Laou, Persefoni (2007)
The purpose of this study is to analyse the Greek Cypriot banking sector from the time that the first bank was established in the island until today. The study will concentrate to the reforms and restructures that banking sector had undergone, after accession of Cyprus to the European Union, on 1 May 2004, and also the reforms that the banking sector will undergo after and during the process of the adaptation of euro as the official currency, on 1 January 2008. Finally an analysis of the performance of banks before and after the EU will be given.